2012
DOI: 10.1007/s10653-012-9449-z
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in the coastal soils developed from estuarine floodplain sediments in the Croatian Mediterranean region

Abstract: Fertile soils in the River Neretva estuary were developed by fluvial sedimentation and deposition of the eroded soil material from the karst hills within the catchment. After extensive reclamation, two reclaimed land zones (fluvial terraces and lower-laying terraces) have been delineated, both used for agriculture. The main objectives of this study were to evaluate soil chemical and geochemical properties in reclaimed zones that differ mainly in topography, soil types and agricultural land use. The origin of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 41 publications
1
30
1
1
Order By: Relevance
“…9.2). IDW uses the measured values surrounding the interpolation points, which are then weighted according to their distance from the point being interpolated (Carr et al 2008;Romic et al 2012). This interpolation is a relatively easy method because it depends on the distance between the sampling sites and prediction points only.…”
Section: Map Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…9.2). IDW uses the measured values surrounding the interpolation points, which are then weighted according to their distance from the point being interpolated (Carr et al 2008;Romic et al 2012). This interpolation is a relatively easy method because it depends on the distance between the sampling sites and prediction points only.…”
Section: Map Productionmentioning
confidence: 99%
“…When the natural and anthropogenic processes affected together in the floodplain, the behavior of heavy metals was likely to change because of the altered environmental conditions (Romic et al 2012). The presence of metals, like Cu, Zn, or Pb, might be partly attributed to sediment deposition brought by river flow and partly attributed to anthropogenic interventions after reclamation.…”
Section: Enrichment Status Of Heavy Metals In Different Reclamation Zmentioning
confidence: 99%
“…Trace metals may get segregated between fluvial morphologic units due to hydraulic sorting by size and density and due to the different residency time of sediments in different units (Ladd et al 1998). Studying the relation between trace metals concentration in arable soils of two reclaimed land zones (fluvial terraces and polder-type lower-laying terraces) in the study region, Romic et al (2012) found that soils on the fluvial terraces developed from the mixed dredged sediments have higher Cd and Cu concentrations, which is apparently caused by specific land use and traditional agricultural practice.…”
Section: Discussionmentioning
confidence: 99%
“…Surface Quaternary sediments consist mainly of peat and clay (organic marshy deposits), which are underlain by clayey sands, sands of variable grain size, sandy clay, gravelly sands, sandy gravel and Holocene gravels (alluvial sediments), as well as Pleistocene conglomerates. Geomorphology, soil characteristics and reclamation in the study area are described in detail by Romic et al (2012). Agriculture is the main activity in the area of the River Neretva delta, primarily dominated by vegetable production and citrus growing applying irrigation.…”
Section: Study Sitementioning
confidence: 99%
“…Borůvka and Kozák (2001) reported that spatial heterogeneity of coastal plain soils differed greatly from that of natural soils due to their anthropogenic origin. With the rapid development of agriculture and industry after reclamation, excessive agro-chemical inputs into these soils can impose a long-term burden on the biochemical cycle (Romic et al, 2012). Li et al (2008) concluded that land use changes in reclaimed regions resulted in soil quality changes and that a redistribution of materials and energy occurred.…”
Section: Introductionmentioning
confidence: 99%